Potential health risks to disinfection workers from exposure to active substances in COVID-19 biocidal products - Gihong Min; Jihun Shin; Dongjun Kim; Youngtae Choe; Jaemin Woo; Kil Yong Choi; Jangwoo Lee; Mansu Cho; Jongdae Lee; Jin-Sung Ra; Wonho Yang (Heliyon, 2024)
The importance of disinfection has recently been emphasized due to the increasing risk of the spread of infections such as coronavirus disease-2019 (COVID-19). In addition, disinfection for preventing the spread of COVID-19 is highly recommended. The increased use of biocidal products raises concerns regarding the potential health risks from exposure among disinfection workers. This study aimed to assess these exposure and health risks using questionnaires targeting disinfection workers who were exposed to the active substances in biocidal products used for disinfection during the COVID-19 pandemic. A follow-up survey was conducted among 271 disinfection workers for 10 working days within two weeks, and exposure factors with reference to disinfection were evaluated through interview-administered questionnaires. An exposure algorithm was used to evaluate the exposure of disinfection workers during disinfection. The hazard index (HI) was calculated by dividing the inhalation concentration obtained using the exposure algorithm and the dermal dose according to occupational exposure limits (OEL). A sensitivity analysis was conducted to identify the exposure factors with the greatest impact on the inhalation and dermal exposure algorithms. A logistic regression analysis was performed to verify the relationship with health effects and sociodemographic and exposure characteristics. The average number of disinfections performed during 10 working days was 17.5 ± 12.3 times. The type of disinfection work was divided into 2806 cases of COVID-19 prevention and disinfection and 1956 cases of regular pesticide application to prevent and remove any pests. The HI was ≥1, indicating a potential health risk, with the use of ethanol (6.50E+00), quaternary ammonium compounds (QACs; 1.49E+01), and benzalkonium chloride (BKC; 1.73E+00). Dermal exposure was more hazardous than inhalation exposure for 6 of the 11 active substances in biocidal products. The weight fraction and exposure time were the factors that most significantly influenced the inhalation and dermal exposure algorithms in the sensitivity analysis. Higher exposure concentrations were more likely to affect health (AOR: 3.239, 95% CI: 1.155–9.082). This study provides valuable information regarding the exposure and risk of disinfection workers to 11 biocidal active substances included in common disinfectants. Our results suggest that the use of ethanol, BKC, and QACs has potential health risks to disinfection workers, with a higher possibility of negative health impacts with increasing exposure concentration.